2021
DOI: 10.1002/adma.202100978
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photoconductivity and Terahertz Vibrational Dynamics in Double‐Helix SnIP Nanowires

Abstract: SnIP could be the first of a new class of inorganic double-helix materials. [7][8][9] With strong intra-helix covalent bonds and weak inter-helix dispersion forces, SnIP belongs to the group of newly emerging 1D van der Waals (vdW) materials with potential applications in nanoelectronics and photonics. [10][11][12][13] In contrast to the DNA structure, which consists of two equal radius helices, SnIP forms with an outer [SnI] + helix wrapping around an inner [P] − helix, as pictured in Figure 1a. SnIP crystall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…33 Time-resolved terahertz (THz) spectroscopy revealed a high intrinsic electron mobility along the double-helix axis, which is limited by traps. 35 Individual SnIP double-helix strands can be obtained from the racemic mixture by minimizing the van de Waals force and stabilizing the single strands in a different medium, such as in SnIP@C 3 N 4 (F,Cl) thin films. 33 Another possibility, as indicated by total energy calculations, 33,36 is the encapsulation of individual strands in carbon nanotubes.…”
Section: ■ Model Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Time-resolved terahertz (THz) spectroscopy revealed a high intrinsic electron mobility along the double-helix axis, which is limited by traps. 35 Individual SnIP double-helix strands can be obtained from the racemic mixture by minimizing the van de Waals force and stabilizing the single strands in a different medium, such as in SnIP@C 3 N 4 (F,Cl) thin films. 33 Another possibility, as indicated by total energy calculations, 33,36 is the encapsulation of individual strands in carbon nanotubes.…”
Section: ■ Model Systemmentioning
confidence: 99%
“…In addition, the material is highly flexible and stable, showing polymer-like behavior . Time-resolved terahertz (THz) spectroscopy revealed a high intrinsic electron mobility along the double-helix axis, which is limited by traps . Individual SnIP double-helix strands can be obtained from the racemic mixture by minimizing the van de Waals force and stabilizing the single strands in a different medium, such as in SnIP@C 3 N 4 (F,Cl) thin films .…”
Section: Model Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The primitive cell of SnIP contains a le-and a right-handed double helix bonded by weak van der Waals (vdW) interactions, with each double helix having a small [P] helix nested into the relatively larger [SnI] helix. The unique structure makes SnIP show both interesting electronic properties such as high carrier mobility as a typical inorganic semiconductor 18,19 and distinctive mechanical properties such as high exibility, deformability, and especially a remarkably low Young's modulus (13.6 GPa) as a stable inorganic material. 20 Recent studies revealed that SnIP also has special topological properties which can exhibit topological nodal rings/ lines in both the bulk phonon modes and their corresponding surface states.…”
Section: Introductionmentioning
confidence: 99%
“…The formation mechanism and stacking motives have been published recently, , while the effect on intra- and interhelical bonding relations and their influence on each other after hybrid material formation are still somewhat uncertain. Recently, time-resolved terahertz spectroscopy was used to investigate the transient photoconductivity and charge carrier mobility in SnIP . An electron mobility of 280 cm 2 V –1 s –2 along and a hole mobility of 238 cm 2 V –1 s –2 perpendicular to the SnIP double helices were detected.…”
Section: Introductionmentioning
confidence: 99%